Pengembangan Buku Ajar Bahasa Arab Berbasis pada Nilai-Nilai Islam-Indonesia di IAIN Salatiga - Habibi, Burhan Yusuf; Putri, Wakhidati Nurrohmah (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2021)
This study aims to develop Arabic language teaching materials 1 based on Islamic-Indonesian values ​​at the State Islamic Institute of Slaatiga. This research is motivated by the lack of specific teaching materials for this course after transferring status from STAIN to IAIN and learning Arabic was returned to the faculty. This research is a type of research and development with the Borg & Gall development model. The analysis technique in this study uses quantitative descriptive techniques. The results showed that the results of student responses to the Arabic Textbook 1 Based on Islamic-Indonesian Values ​​at the Salatiga State Islamic Institute which was developed viewed from the learning aspect obtained an average score of 4.025, the content or material aspect with an average score average 4.095, aspects of the display with an average score of 4.098 and aspects of the presentation with an average score of 4.08, then the overall average score is 4.075. Thus, Arabic textbook based on Islamic-Indonesian values ​​is worthy of being used as teaching material in the Arabic language course 1 at the Salatiga State Islamic Institute.